2013
DOI: 10.1007/s10464-013-9578-2
|View full text |Cite
|
Sign up to set email alerts
|

A Little Goes a Long Way: The Impact of Distal Social Support on Community Integration and Recovery of Individuals with Psychiatric Disabilities

Abstract: Although an extensive body of literature highlights the important role of social support for individuals with psychiatric disabilities, definitions of support tend to be restricted-focusing on intimate relationships such as friend and family networks and ignoring the role of casual relationships existing naturally in the community. This mixed-methods study of 300 consumers of mental health services in the Southeastern US aims to better understand the impact of community supports, termed distal supports, on com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 54 publications
4
50
0
3
Order By: Relevance
“…For example, the scope of the setting in which intervention occurs may be critical to treatment outcomes. Townley et al (2013) distinguished between proximal social support (from close personal relationships) and distal social support (from the community) for individuals with psychological diagnoses, and found that communities played a distinct and important role in providing tangible support such as discounted medication. These distinctions are non-trivial in terms of their implications for mental health outcomes; mentally-ill individuals' perceptions of their own neighborhood's quality predict their personal well-being (Townley and Kloos 2014).…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, the scope of the setting in which intervention occurs may be critical to treatment outcomes. Townley et al (2013) distinguished between proximal social support (from close personal relationships) and distal social support (from the community) for individuals with psychological diagnoses, and found that communities played a distinct and important role in providing tangible support such as discounted medication. These distinctions are non-trivial in terms of their implications for mental health outcomes; mentally-ill individuals' perceptions of their own neighborhood's quality predict their personal well-being (Townley and Kloos 2014).…”
Section: Future Directionsmentioning
confidence: 99%
“…Specifically, the trend toward supported housing, marked by principles of consumer choice, holding a lease to community-based housing, and availability of flexible services, is a preferred alternative to residential treatment facilities or long-term institutional treatment (Carling 1993;Nelson et al 2001;Ridgway and Zipple 1990). Community integration encompasses individuals' opportunities to participate in meaningful community activities, interact with community members, and experience a sense of community, or a sense of belonging to the broader community in which they reside (Townley et al 2013;Wong and Solomon 2002). Community integration encompasses individuals' opportunities to participate in meaningful community activities, interact with community members, and experience a sense of community, or a sense of belonging to the broader community in which they reside (Townley et al 2013;Wong and Solomon 2002).…”
Section: The Social Ecology Of Supported Housing Environmentsmentioning
confidence: 99%
“…A major distinguishing feature of the supported housing model is an emphasis on community integration, in which consumers move from being clients primarily to being citizens who are engaged in, supported by, and contributing to their communities (Carling 1995;Nelson and Peddle 2005;Ridgway and Zipple 1990). Community integration encompasses individuals' opportunities to participate in meaningful community activities, interact with community members, and experience a sense of community, or a sense of belonging to the broader community in which they reside (Townley et al 2013;Wong and Solomon 2002).…”
Section: The Social Ecology Of Supported Housing Environmentsmentioning
confidence: 99%
“…Several articles compared the treatment effectiveness of different programs aimed at supporting individuals with serious mental illnesses as they transitioned out of psychiatric hospitals (e.g., Berman & Hoppe, ; Nelson, Hall & Walsh‐Bowers, ; Tsai, Stroup & Rosenheck, ). Articles in this category also focused on social‐environmental influences on community integration and recovery (e.g., Townley, Miller & Kloos, ). Articles in this category were published between 1973 and 2015, with equal distribution across the four decades.…”
Section: Resultsmentioning
confidence: 99%